Integration of Islamic Moderation Values on Islamic Education Learning Material at Madrasah Aliyah Level - Amrullah Amrullah (AJIS: Academic Journal of Islamic Studies, 2022)
This research aims to discover and to describe the pattern of integration of Islamic moderation values on material of Islamic education learning at Madrasah Aliyah Level. This research used qualitative method with the literature approach. This research began by collecting primary and secondary sources, followed by categorizing library sources based on research needs, collecting library resources data, displaying data as findings, abstracting data as of becoming facts, analyzing facts and ultimately obtaining the research results in the form of new information. The results of the research indicate that the pattern of integration between Islamic moderation values and material of Islamic education are able to be conducted through four moves, describing the religious moderation values in detailed which are obtained from various supporting sources, classifying Islamic moderation values to be linked into Islamic material education, integrating its moderation values into Islamic material education and incorporating the religious moderation values into the evaluation of learning. The Islamic moderation values which are conveyed in teaching and Islamic education learning taught to students are conducted gradually, either by direct learning or by self-learning by using teaching’s material. Islamic moderation values are more convenient to be linked with Islamic education learning, as the content is much related to materials of Islamic education.